The fate of liberal arts in today's schools and colleges - Hayes, William, 1938- (Rowman & Littlefield, 2015)
The book will highlight the arguments of both points of view. In doing so, attention will be paid to the contributions to society of those who have been exposed to a variety of educational curricula. As part of the study, the impact of the community college will be considered, along with the impact of recent initiatives such as the Nation at Risk Report, No Child Left Behind, Race to the Top, and the Common Core. Finally, the text will conclude with an attempt to suggest the direction that will determine the fate of liberal arts in schools and colleges.